Cross-Protection Against Four Serotypes of Dengue Virus in Mice Conferred by a Zika DNA Vaccine - Wang, Ran; Gao, Na; Li, Yun; Fan, Dongying; Zhen, Zida; Feng, Kaihao; Chen, Hui; An, Jing (Frontiers in Cellular and Infection Microbiology, 2019)
Both Zika virus (ZIKV) and four serotypes of dengue virus (DENV1–4) are antigenically related mosquito-borne flaviviruses that co-circulate in overlapping geographic distributions. The considerable amino acid sequence homology and structural similarities between ZIKV and DENV1–4 may be responsible for the complicated immunological cross-reactivity observed for these viruses. Thus, a successful Zika vaccine needs to not only confer protection from ZIKV infection but must also be safe during secondary exposures with other flavivirus, especially DENVs. In this study, we used a Zika DNA vaccine candidate (pV-ZME) expressing the ZIKV premembrane and envelop proteins to immunize BALB/c mice and evaluated the potential cross-reactive immune responses to DENV1–4. We observed that three doses of the pV-ZME vaccine elicited the production of cross-reactive antibodies, cytokines and CD8+ T cell responses and generated cross-protection against DENV1–4. Our results demonstrate a novel approach for design and development of safe Zika and/or dengue vaccines.